Indirect tail states formation by thermal-induced polar fluctuations in halide perovskites - Wu, Bo (2019)
Halide perovskites possess enormous potential for various optoelectronic applications. Presently, a clear understanding of the interplay between the lattice and electronic effects is still elusive. Specifically, the weakly absorbing tail states and dual emission from perovskites are not satisfactorily described by existing theories based on the Urbach tail and reabsorption effect. Herein, through temperature-dependent and time-resolved spectroscopy on metal halide perovskite single crystals with organic or inorganic A-site cations, we confirm the existence of indirect tail states below the direct transition edge to arise from a dynamical Rashba splitting effect, caused by the PbBr6 octahedral thermal polar distortions at elevated temperatures. This dynamic effect is distinct from the static Rashba splitting effect, caused by non-spherical A-site cations or surface induced lattice distortions. Our findings shed fresh perspectives on the electronic-lattice relations paramount for the design and optimization of emergent perovskites, revealing broad implications for light harvesting/photo-detection and light emission/lasing applications.